People of the polar north; a record comp. from the Danish originals and ed. by G. Herring. - Rasmussen, Knud Johan Victor, 1879-1933. (Philadelphia, Lippincott, 1908)
Published in Danish under the titles "New people" & "Under the lash of the north wind." Mode of access: Internet.